Cognitive Impairment during High-Intensity Exercise: Influence of Cerebral Blood Flow - Komiyama, Takaaki; Tanoue, Yukiya; Sudo, Mizuki; Costello, Joseph T; Uehara, Yoshinari; Higaki, Yasuki; Ando, Soichi (Medicine and science in sports and exercise, 2020)
Cognitive performance appears to be impaired during high-intensity exercise, and this occurs concurrently with a reduction in cerebral blood flow (CBF). However, it is unclear whether cognitive impairment during high-intensity exercise is associated with reduced CBF. We tested the hypothesis that a reduction in CBF is responsible for impaired cognitive performance during high-intensity exercise. Using a randomized crossover design 17 healthy males performed spatial delayed response and Go/No-Go tasks in three conditions (exercise [EX], exercise+CO2 [EX+CO2], and a nonexercising control [CON]). In the EX and EX+CO2, they performed cognitive tasks at rest and during 8 min of moderate and high-intensity exercise. Exercise intensity corresponded to ~50% (moderate) and ~80% (high) of peak oxygen uptake. In the EX+CO2, the participants inspired hypercapnic gas (2% CO2) during high-intensity exercise. In the CON, they performed the cognitive tasks without exercise. Middle cerebral artery mean velocity increased during high-intensity exercise in the EX+CO2 relative to the EX (69.4 [10.6] cm·s, vs 57.2 [7.7] cm·s, P < 0.001). Accuracy of the cognitive tasks was impaired during high-intensity exercise in the EX (84.1% [13.3%], P < 0.05) and the EX+ CO2 (85.7 [11.6%], P < 0.05) relative to rest (EX: 95.1% [5.3%], EX+CO2: 95.1 [5.3%]). However, no differences between the EX and the EX+CO2 were observed (P > 0.10). These results demonstrate that restored CBF did not prevent cognitive impairment during high-intensity exercise. We conclude that a reduction in CBF is not responsible for impaired cognitive performance during high-intensity exercise.